Market of the Russian avant-garde painting: investment potential and characteristics of auctioning - D. L. Morozova (Вестник университета, 2024)
In Russia, art trading on auctions is considered to have features of the developing market that does not always follow global trends. Given that the potential of studying the national art market is not sufficiently fulfilled, the author has set the following purposes in this article: to study characteristics of investing in the Russian avant-garde artists and to build an econometric model (on the example of the “Knave of Diamonds” society). The Russian avantgarde is for the first time examined as an area forming general and unique pricing trends. The article analyses the peculiarities and trends of demand for avant-garde painting in 2000–2021, describes the geography of auction sales as well as the level of liquidity of art assets and provides price dynamics of the national and world markets. For these purposes, statistical analysis and visualisation are used, an econometric model is built using censored Heckman regression (Tobit-2). The average yield of M.Z. Chagall’s oil painting has been calculated in the article with the method of repeat sales. The nominal yield of his works, according to the author’s calculations, is 5.1 % which significantly lags behind the same indicator of financial assets. Investing in painting is viewed as a complex phenomenon with unique properties that distinguish the art market from other investments. The article is addressed to investment managers, bankers, collectors, appraisers, and specialists in economy of art.